The power actor and madrasah performance: Political connections as a moderating variable - Rahmawaty; I Made Narsa (Economies, 2022)
With the background of public sector management reform in the world of education, the characteristics of the leaders have become the main thing in improving an institution's performance theory; this study explores the influence of aspects of the heads of madrasah (their age, education, and tenure) and madrasah performance in Islamic educational institutions in East Java, Indonesia. This study shows that political relations strengthen the positive influence of the head's age and tenure on madrasah performance. Meanwhile, political connections do not enhance the positive impact of the madrasah head's formal educational background on madrasah performance.
Keywords: 330; madrasah performance; political connections; power actors; upper echelon theory